PUBLIC SECTOR EMPLOYEES’ MOTIVATION: CAUSES AND EFFECTS - Serhan, Carole; Achy, Eliane Al; Nicolas, Eva (PEOPLE: International Journal of Social Sciences, 2018)
This article aims to examine the causes and effects of public sector employees’ motivation. A qualitative interview is performed among Lebanese managers and employees working in public organizations to understand their standpoints in relation to the key dimensions which could affect work motivation and how these dimensions could affect their work effectiveness and involvement. In view of the above, this research identifies the dimensions that most affect motivation at work and highlights the related consequences. Results show that there is a strong support for pay and working conditions as predictors of public sector employees’ motivation, work effectiveness and involvement. Finally, guidelines and recommendations for implementing research findings are provided.